MEDIATION AS A TOOL FOR CONFLICT RESOLUTION IN THE CONTEXT OF JUDICIAL SYSTEM CHALLENGES DURING WAR - Miakotina, Vladyslava; Olendra, Nataliia (Collection of scientific papers «ΛΌГOΣ», 2025)
In the context of martial law in Ukraine, there is an urgent need to prevent/level conflict situations. However, sometimes there are circumstances in which it is difficult for the parties to resolve the conflict, and this is when the need to involve a third party arises: representatives of central or local government, lawyers, mediators, auditors, etc.